Availability and use of institutional support programs for emergency department healthcare personnel during the COVID-19 pandemic. - Karin F Hoth; Patrick Ten Eyck; Karisa K Harland; Anusha Krishnadasan; Robert M Rodriguez; Juan Carlos C Montoy; Linder H Wendt; William Mower; Kelli Wallace; Scott Santibañez; David A Talan; Nicholas M Mohr; et al. (PLoS ONE)
Objectives The COVID-19 pandemic placed health care personnel (HCP) at risk for stress, anxiety, burnout, and post-traumatic stress disorder (PTSD). To address this, hospitals developed programs to mitigate risk. The objectives of the current study were to measure the availability and use of these programs in a cohort of academic emergency departments (EDs) in the United States early in the pandemic and identify factors associated with program use. Methods Cross-sectional survey of ED HCP in 21 academic EDs in 15 states between June and September 2020. Site investigators provided data on the availability of 28 programs grouped into 9 categories. Individual support programs included: financial, workload mitigation, individual COVID-19 testing, emotional (e.g., mental health hotline), and instrumental (e.g., childcare) Clinical work support programs included: COVID-19 team communication (e.g., debriefing critical incident), patient-family communication facilitation, patient services (e.g., social work, ethics consultation), and system-level exposure reduction. Participants provided corresponding data on whether they used the programs. We used generalized linear mixed models clustered on site to measure the association between demographic and facility characteristics and program use. Results We received 1,541 survey responses (96% response rate) from emergency physicians or advanced practice providers, nurses, and nonclinical staff. Program availability in each of the 9 categories was high (>95% of hospitals). Program use was variable, with clinical work support programs used more frequently (28-50% of eligible HCP across categories) than individual employee support programs (6-13% of eligible HCP across categories). Fifty-seven percent of respondents reported that the COVID-19 pandemic had affected their stress and anxiety, and 12% were at elevated risk for PTSD. Program use did not significantly differ for HCP who reported symptoms of anxiety and/or stress compared to those who did not. Conclusions Early in the pandemic, support programs were widely available to ED HCP, but program use was low. Future work will focus on identifying barriers and facilitators to use and specific programs most likely to be effective during periods of highest occupational stress.